PERCEPTION OF THE IMPACT OF THE MENSTRUAL CYCLE ON THE CREATIVITY OF MEDICAL STUDENTS AT A MEXICAN UNIVERSITY - Martínez-Oportus, Ximena Paz; García, Agustín Anaya; Sepúlveda, Juan Mancilla (Journal of Posthumanism, 2025)
The present research aimed to map and identify the perception of creativity among undergraduate students at a Mexican university, explicitly focusing on Medicine. The objective was to comprehensively analyze how these perceptions could vary according to the phases of the menstrual cycle, comparing the results with surveys administered to creativity specialists. The research addressed the need to adapt equality and gender policies for greater flexibility in microcurricular academic processes that often prove rigid. A mixed-methods approach was designed to achieve this, combining quantitative surveys with qualitative interviews. In the quantitative phase, data were collected from Medicine students to analyze patterns and trends in the perception of creativity during the different stages of the menstrual cycle. In the qualitative phase, semi-structured interviews were conducted with students and experts in neuroscience and creativity, allowing for an in-depth exploration of individual experiences. The triangulation of quantitative and qualitative data reinforced the validity of the findings. The research suggested significant differences in the perception of creativity, motivation, and the ability to synthesize ideas depending on the participants' different phases of the menstrual cycle. As a result, a model of adaptation and methodological strategies based on agile methodologies, such as design thinking, was proposed to enhance flexibility and equity in the academic environment. This approach could transform how creative and educational dynamics are managed and addressed in university contexts.